Negative βhCG and Molar Pregnancy: The Hook Effect - Lobo Antunes, Isabel (2017)
Molar pregnancy, included in gestational trophoblastic disease, is a benign pathology with ability to metastasize, usually occurring with excessively high βhCG levels. Clinical scenario is usually a woman in extremes of reproductive age presenting with amenorrhoea, pain and vaginal blood loss; signs derived from high βhCG levels may be present (hyperthyroidism, hyperemesis). Diagnosis is based on a positive pregnancy test – usually a qualitative urinary test. The limitation of this test results from its inability to become positive in presence of markedly high levels of βhCG, saturating the antigens used – known as the ‘hook effect’. With the widespread use of gynaecological ultrasound cases of molar pregnancy have been diagnosed in timely fashion. We describe a case referred as a degenerating fibroid, with a negative urinary pregnancy test. Transvaginal ultrasound was highly suggestive of molar pregnancy, which was confirmed with a quantitative βhCG test, allowing for timely treatment. The importance of a high index of suspicion for this pathology is tremendous to avoid the devastating consequences of a delayed diagnosis.